Evaluation of the relationship of chronotype, MIND diet, and lifestyle factors in overweight and obese people: Path analysis and structural equation modeling - Coskun, Ayfer Beyaz; Yilmaz, Feray Cagiran; Acik, Murat (Taylor & Francis Inc, 2025)
The effects of chronotype and diet on obese individuals have been reported in previous studies. This study aimed to examine the relationship between the Mediterranean-DASH intervention for neurodegenerative delay (MIND) diet, chronotype and lifestyle factors in different types of overweight and obese people. 1100 obese individuals participated in this cross-sectional study. Compliance with the MIND diet was questioned, anthropometric measurements were taken, and biochemical parameter results from patient records in the last week were examined. Chronotypes were determined with the A self-assessment questionnaire to determine morningness in human circadian rhythms scale. MIND diet score was inversely associated with the body mass index (BMI) [beta (SE) = -0.239 (0.11), p = 0.31] and waist circumference [beta (SE) = -0.026 (0.01), p = 0.028], explained 0.4% of BMI and 0.6% of WC. There was a significant relationship between poorer MIND diets and higher CRP levels. A positive correlation was found between an increased MEQ score and MIND diet only in overweight participants (correlation coefficient = 0.200, p < 0.05). Whole cereals and fish consumption were positively associated with chronotype scores, while the highest odds of red meats and fast/fried foods seemed to have a negative effect. As a result, it has been observed that individuals with a morning chronotype have higher compliance with the MIND diet and make healthier food choices. Both having a morning chronotype and complying with the MIND diet have been associated with improvements in biochemical parameters in overweight and obese people.
Keywords: MIND diet; chronotype; metabolic health; Obesity; overweight; lifestyle factors